Minority community college CEOs perceptions of underrepresentation, preparation and ascension to the presidency - Hines, CharMaine Y. (Kansas State University, 2021)
This phenomenological study explored the perceptions of thirty-four CEOs of color of the underrepresentation of minorities serving in presidential roles at community colleges. Research has identified an underrepresentation of race and gender diversity among community college presidents that fails to mirror the racial and ethnic diversity of community college students today. Historically and currently, the majority of presidents in American community colleges have been older white males. An analytical review of the research shows scant progress in diversifying minority-serving community college presidents, creating a need to understand leakage points in the pipeline to the presidency relevant to understanding the underrepresentation of minority community college presidents. This qualitative study used Critical Race Theory (CRT) and Glass Ceiling theoretical frameworks. Thirty-four CEOs of color participated, representing diverse ethnic backgrounds, including African American, Asian Pacific Islander, and Latino/Hispanic, and spanning twelve states and every region of the U.S. In semi-structured interviews, the CEOs described their perceptions of the underrepresentation of minorities among the ranks of community college presidents, their ascension to the presidency, and the leadership preparation necessary for attaining the presidency in community colleges. Multiple steps were used to conduct the data analysis. Counter-narratives were examined using a modified interpretative phenomenological approach (IPA) concept model the researcher expanded creating a nine (9) step system of data collection and analysis for the. Using the Pew Research Center’s (2020) classification and name of generations as a guide, the researcher coupled and aligned each participant by both generations of the American community college, development (Deegan and Tillery, 1985; Geller, 2001) with distinct characteristics of generations of community college leadership style (Sullivan, 2001; Boggs and McPhail, 2016) hence updating the generation definitions and naming conventions. An analysis of the study determined the current focus of community college leadership development is more Equity Centered labeling the 4th generational style as Transformers and the 5th generation as Equity Achievers. What emerged were rich counter-stories and voices from Gen X and Gen X II/Millennials I leaders providing a unique perspective from this newest and little-explored generation of leaders. Findings arranged by composite, gender, and ethnicity groups retained participants’ authentic voices. An analysis of the data identified significant themes that illustrate leaders’ perceptions of challenges, barriers, and biases that contribute to the underrepresentation of minorities serving in presidential roles in community colleges. Themes included structural barriers within institutional culture, biased perceptions of race, and gender and systemic racism. Findings from the study indicate that the leadership development system that served a movement in the second half of the 20th century may be insufficient for addressing ongoing underrepresentation in the 21st century. Findings identified including lack of a clear pathway to the presidency, evidence of a leaky pipeline, a flawed hiring process and gatekeepers along the continuum, opportunity, access, support, mentors, and intentional leadership development. Systemic biases and structural racism, a glass ceiling for men and women of color, and socio-political forms of oppression as microaggressions, tokenism, invisibility, the Imposter Syndrome, and John Henry-ism. This study identified numerous deficiencies that impact the underrepresentation of minorities in the community college presidency offering sixteen (16) recommendations to improve practice. Recommendations included the role of university-based leadership preparation programs, a call to action for regional, state, and national associations and affiliate councils, and examining the role of boards of trustees and governing boards in leading the charge for diverse leadership. This study makes a practical, theoretical, and social contribution to the study of the underrepresentation of race and gender diversity in the community college presidency provides insight into the myriad of factors identified, gives voice to the newest generation of leaders, and discusses implications for future research and practice.
Keywords: Minority community college presidents; African American; Critical race theory; Glass ceiling; Asian Pacific Islander; Latino/Hispanic